Amyotrophic lateral sclerosis : understanding and optimizing quality of life and psychological well-being - Pagnini, Francesco; Simmons, Zachary ([Oxford] : Oxford University Press, 2018)
This work provides clinicians with a comprehensive description of the psychological aspects of ALS and their management, and incorporates chapters written by recognized scholars in their respective fields.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 20, 2018).
Keywords: Amyotrophic lateral sclerosis -- Psychological aspects; Amyotrophic lateral sclerosis